PENGARUH POLA ASUH ORANG TUA DEMOKRATIS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS VII SMPN 1 SITUBONDO - Irma Noervadila; Anisa Meiliana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2019)
Proper education and care for children will result in the birth effect of achieving children. Therefore, one of the most important things parents do is to know what principles need to be adhered to in order for parents to succeed in educating children and also how to successfully educate children, including parents who have little time to educate his children. Based on the problems above, the authors are interested to make the title